1997
DOI: 10.1016/s0009-9236(97)90185-5
|View full text |Cite
|
Sign up to set email alerts
|

Temporal decline in filling prescriptions for terfenadine closely in time with those for either ketoconazole or erythromycin*

Abstract: Temporal changes in the rates of filling terfenadine prescriptions within 2 days of those for either oral erythromycin or oral ketoconazole were described with use of paid pharmacy claims data from 1988 through 1994 in state Medicaid programs from Michigan and Ohio and in a large health maintenance organization. There were rapid and significant declines in the rates of filling prescriptions for either erythromycin or ketoconazole within 2 days of prescriptions for terfenadine in all three databases that coinci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 5 publications
0
18
0
Order By: Relevance
“…For example, several studies suggested the largest declines in cisapride co-prescribing occurred following the FDA’s third such warning (2023), although not all studies indicated such a change (24). Declines in terfenadine co-prescribing also occurred although the largest effects were not observed until 18 months or more following the initial warnings (2527). Only one study concluded there was an increase in terfenadine co-prescribing between 1991 and 1992, although the authors examined absolute rather than relative co-prescribing events (28).…”
Section: Resultsmentioning
confidence: 99%
“…For example, several studies suggested the largest declines in cisapride co-prescribing occurred following the FDA’s third such warning (2023), although not all studies indicated such a change (24). Declines in terfenadine co-prescribing also occurred although the largest effects were not observed until 18 months or more following the initial warnings (2527). Only one study concluded there was an increase in terfenadine co-prescribing between 1991 and 1992, although the authors examined absolute rather than relative co-prescribing events (28).…”
Section: Resultsmentioning
confidence: 99%
“…However, multiple attempts by regulatory agencies and drug companies to limit the administration of dangerous combinations, such as cisapride and erythromycin, have been only transiently successful. [75][76][77] Prescribers should recognize that most drugs have multiple, and often unanticipated, actions. In addition, even drugs that are designed to interact with a single molecular target act in a complex biologic milieu.…”
Section: Basic Electrophysiological Mechanismsmentioning
confidence: 99%
“…The identification of a very small number of cases of diLQTS, however, markedly upset the risk-benefit calculations for the drug: the publically promulgated regulatory view was that the drug was prescribed for a nonlethal indication (allergies) and that even a small risk of a fatal adverse drug reaction was therefore unacceptable. Attempts by regulatory authorities (Burkhart et al, 1997) to make physicians and the public aware of the dangers of drug interactions with terfenadine, including black box warnings and educational programs, were ultimately unsuccessful (Cavuto et al, 1996;Thompson and Oster, 1996;Woosley, 2000) and when fexofenadine was approved for therapy, terfenadine was withdrawn.…”
Section: F Impact Of Qt Prolongation On Drug Developmentmentioning
confidence: 99%